Legal Provisions for Handing Over Part of a Civil Servant's Salary to His Ex-Wife from an Islamic Law Perspective - Asrofi; Oyo Sunaryo Mukhlas (al-Afkar, Journal For Islamic Studies, 2024)
Islam views the marriage contract as a miitsaqan ghalidha with the main goal of forming a sakinah mawaddah wa rahmah. Even though the marriage bond is so strong, the reality shows that many marriages have broken up due to divorce, for example in 2021 there will be approximately 459,630 couples, including divorces carried out by PNS, which are also not small. In certain cases of divorce, Islam obliges the husband to provide mut'ah along with maintenance, dowry and kiswa during the iddah period according to the husband's ability and propriety. Specifically for male civil servants, in certain divorce cases, they are also obliged to hand over part of their salary to their ex-wife and children or children, as stipulated in Article 8 PP No. 10 of 1983 jo PP No. 45 of 1990. These provisions need to be examined from the perspective of Islamic law. In researching used normative juridical research. The results of the study according to the authors of the deduction/delivery of part of the male PNS to his ex-wife as stipulated in the Government Regulation are not in accordance with the provisions of Islamic law, for the reasons that, among other things, Islam has determined the obligation for divorced men in certain cases to give to his ex-wife in the form of mut'ah and nafkah iddah, the deduction/delivery of part of the PNS has the potential to violate the objectives of Islamic law to achieve benefits with the aim of, among others, hifdz al maal.